1980
DOI: 10.1136/vr.107.14.326
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella multocida infection of poultry farm rats

Abstract: Thirty-four rat carcases from 11 poultry farms were examined for the presence of Pasteurella multocida; 14 out of 34 (41 per cent) proved positive after mouse inoculation, compared with five out of 34 (14 per cent) using media alone. No salmonellae were recovered from 27 rat carcases using enrichment media. Poultry pasteurellosis was present on two farms with infected rats and the same serotype was present in rats and poultry in those cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Thirdly, mammals are known to host and transmit P . multocida to poultry [ 57 , 58 ], so one could expect the introduced brown rat to play a role in the local circulation of this pathogen. Brown rats were accidently introduced at least one century ago by boats onto the island, where they now roam, including within seabird colonies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, mammals are known to host and transmit P . multocida to poultry [ 57 , 58 ], so one could expect the introduced brown rat to play a role in the local circulation of this pathogen. Brown rats were accidently introduced at least one century ago by boats onto the island, where they now roam, including within seabird colonies.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of bacterial inter-season maintenance and the elucidation of transmission pathways during the breeding seasons must be urgently assessed. The putative role of brown rats as maintenance hosts has been extensively documented in other situations [ 58 60 ] and rats could actually be maintaining the bacteria between breeding seasons while seabirds are absent from the island [ 55 , 56 ]. In addition, rats and seabird chicks are both preyed by brown skuas, which may transmit the bacteria from rodents to albatrosses and between albatrosses.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of rodent control to reducing the risks of infection with pathogens such as Salmonella, Campylobacter and Pasteurella are well known and have been called for in the past (Curtis et al 1980;Meerburg & Kijlstra 2007). However, the implication that AIV may possibly be transmitted by rodents could be an additional motivation for poultry farmers to implement preventive measures, such as effective rodent-proofing of poultry houses.…”
Section: Discussionmentioning
confidence: 99%
“…infections on layer farms between flocks (Umali et al 2012). Rodents have also been implicated in transmission of Pasteurella multocida (Curtis et al 1980;Curtis 1983), Erysipelas, Bordetella, Leptospirosis and Fowl pox virus (Hinkle & Corrigan 2013). Identical isolates of Brachyspira spp.…”
Section: Potential For Contact Between Rodents and Poultrymentioning
confidence: 99%
“…It has been suggested that rats may play a significant part in the epidemiology of pasteurellosis in poultry and that rat bites may account for some primary infections in these birds (Curtis et al, 1980). Experimentally it has been demonstrated that a rat bite can actually transmit infection to domestic poultry (Curtis, 1983).…”
Section: Introductionmentioning
confidence: 99%